2007
DOI: 10.1007/s00542-007-0409-y
|View full text |Cite
|
Sign up to set email alerts
|

Analytical investigation and numerical verification of Casimir effect on electrostatic nano-cantilevers

Abstract: In this paper, the two-point boundary value problem (BVP) of the nano-cantilever deflection subjected to Casimir and electrostatic forces is investigated using analytical and numerical methods to obtain the instability point of the nano-beam. In the analytical treatment of the BVP, the nonlinear differential equation of the model is transformed into the integral form by using the Green's function of the cantilever beam. Then, closed-form solutions are obtained by assuming an appropriate shape function for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(20 citation statements)
references
References 19 publications
(13 reference statements)
1
19
0
Order By: Relevance
“…Now, by Considering the first order fringing field correctness effect the electrostatic force per unit length of the beam is written as the following (Ramezani et al, 2008):…”
Section: 2 Work Of External Forcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, by Considering the first order fringing field correctness effect the electrostatic force per unit length of the beam is written as the following (Ramezani et al, 2008):…”
Section: 2 Work Of External Forcesmentioning
confidence: 99%
“…In distance less than few micrometers, Casimir force significantly affects the nano-beams stability. Casimir force between two plates can be explained via electromagnetic quantum vacuum fluctuations and motion of virtual photons between two conductive surfaces (Lifshitz, 1956) .In recent years, various approaches such as experimental measurements (Buks et al, 2001a;2001b), using finite element methods (Moghimi Zand et al, 2010;Tadi Beni et al, 2013), experimental observations (Wilson and Beck, 1996;Sundararajan and Bhushan, 2002), applying classic continuum theory (Ramezani et al, 2008;2007;Farrokhabadi et al, 2013;, semi-analytical approaches Koochi and Abadyan 2011;Duan et al, 2013) are utilized to investigate the effect of Casimir force on performance of nano-systems. Another dispersion force that is dominant in nano-scales is the vdW force that affects the stability of nano-structures.…”
Section: Introductionmentioning
confidence: 99%
“…When double-sided actuator exhibits large displacements, the curvature of the de ection should be considered; therefore, governing changes into [54]:…”
Section: Appendix a Large Deformation Theorymentioning
confidence: 99%
“…And they always exist between two objects close to each other. The influence of vdW and Casimir forces on the stability of the MEMS and NEMS actuators with suspended structures has been extensively reported in many literatures [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Chan et al [10] showed that Casimir force can be used to actuate the NEMS devices under certain condition.…”
Section: Introductionmentioning
confidence: 99%
“…Gusso and Delben [18] performed a theoretical analysis focusing on the effect of the Casimir force on the pull-in parameters of electrostatic torsional actuators made from silicon. Ramezani and coworkers [19] investigated the two-point boundary value problem (BVP) of the nano-cantilever deflection subjected to Casimir and electrostatic forces, and derived the instability point of the nanobeam by using analytical and numerical methods.…”
Section: Introductionmentioning
confidence: 99%